Effects of Plyometric Exercises versus Flatfoot Corrective Exercises on Postural Control and Foot Posture in Obese Children with a Flexible Flatfoot - Hatem H. Allam (Hindawi Limited, 2021)
Background. Obesity contributes to the acquired flatfoot deformity which in turn impairs balance. Aim. The purpose of the current study was to compare the effect of plyometric exercises with flatfoot corrective exercises on balance, foot posture, and functional mobility in obese children with a flexible flatfoot. Methods. Forty-seven children participated in the study. Their age ranged from 7 to 11 years. Participants were randomly divided into 3 groups: experimental group I (EGI), experimental group II (EGII), and the control group (CG). The EGI received plyometric exercises and the EGII received corrective exercises, 2 sessions weekly for 10 weeks. The control group did not perform any planned physical activities. The Prokin system was used to assess balance, the timed up and go test (TUG) was used to assess functional mobility, and the navicular drop test (NDT) was used to assess foot posture. Results. EGI showed significant improvement in all balance parameters, foot posture, and TUG. EGII showed improvement in the ellipse area and perimeter in addition to foot posture and TUG. Conclusion. Plyometric exercises and foot correction exercises had a positive effect on foot posture, balance, and functional mobility in obese children with flatfeet.